A review of Quadrimaera Krapp-Schickel & Ruffo, 2000 (Amphipoda: Senticaudata) from Brazil - Alves, Jessika; Neves, Elizabeth; Johnsson, Rodrigo (Zootaxa, 2018)
Two new species of Quadrimaera are described from Brazil. Quadrimaera yemanjae sp. nov. shows article 2 of mandibular palp longer than the others, coxa 1 with anteroventral corner rounded and 8 concavities on gnathopod 2 propodus palm. Quadrimaera miramirandella sp. nov. shows coxa 1 with anteroventral corner rounded and produced, gnathopod 1 with carpus longer than propodus with plumose setae, telson lobes equal in length. New distributional records are reported for Q. cristianae, Q. rocasensis and Q. pieteri. The female of Quadrimaera rocasensis is described for the first time. Quadrimaera pieteri is reviewed and established in Brazil. A taxonomic key of the genus is provided.